Low-income consumers’ experience of stigma in service encounters - Levrini, Gabriel Roberto Dellacasa; Poletti, Lucas (Revista de Administração da UFSM, 2016)
This article focuses on low-income consumers facing social stigma in service encounters with contact employees. Research have regarded the income-consumers from the disadvantaged perspective but few from the stigmatized perspective. The literature tends to propose direct functional relationships between emotions and coping processes. Further studies suggested that emotional and cognitive appraisals interact to influence consumers' choice of coping strategies. Our study was designed using Critical Incident Technique and Content Analysis in 210 low income individuals. The results state the existence of that stigmatized behavior beyond the legitimate expected interaction between the parties involved. The construction of the stigma model evolution illustrated this research.